Facebook spamming among teenagers and its impact on the learning activities at the Madrasah Islamiyah Pangkah Kulon, Ujungpangkah, Gresik - Fahmi, Azizi; Hidayat, Medhy Aginta (C-DISC, 2023)
This article examines the phenomenon of teenage students spamming through Facebook and the impact on their learning activities at Madrasah Tsanawiyah Islamiyah and Madrasah Aliyah Islamiyah, Gresik, Indonesia. This research uses qualitative research methods with a phenomenological approach, and the technique in determining informants is using purposive sampling techniques, and the method in collecting data itself is done through observation and interviews. As a reference in analyzing data and explaining related phenomena in this study, namely using Max Weber's Theory of Action. The results of this study show that students who commit spamming actions are motivated by the economic conditions of their families due to the pandemic and distance learning, as well as the influence of the actions of their friends and the environment around them, with some of the effects experienced by them, namely, often losing focus on learning, not paying attention to class and even sleeping in class during class hours, and skipping class, up to dropping out of school.